Cocriação de valor em repositórios de dados de pesquisa abertos: um estudo das interações entre gestores e pesquisadores no PPBio Data Repository - Remigio, Leonardo Gomes (2022)
In order to understand the co-creation of value in the PPBio Data Repository from the interactions between the repository researchers and managers this research is guided by the following questions: how does the value co-creation process take place in research data repositories (RDR)? How do researchers and managers of the PPBio Data Repository perceive this process? In response to the general objective, the following specific objectives were outlined: a) identify the constructs associated to the process of value co-creation in RDR; b) build an instrument to observe the process of co-creation of value in RDR; c) examine the occurrence of value co-creation practices in the PPBio Data Repository, from the perception of managers and researchers who build the service; and, d) propose guidelines to potentialize the process of value co-creation in the surveyed RDR. Exploratory and descriptive in terms of objectives and qualitative approach, this research undertakes a case study in the RDR of the Programa de Pesquisa em Biodiversidade da Amazônia Ocidental (PPBio AOc), in order to understand the co-creation process in this repository from the perspective of the actors, under the lens of the DART model of value co-creation. The immersion in the literature allowed the identification of the constructs associated to the co-creation of value in the context of RDR and grounded the construction of the ?Study script of the process of co-creation of value in RDR? which, alongside with the semi-structured interview scripts, are presented as a tool for data collection used in this investigation. 12 researchers who use the repository to open scientific data and 2 RDR managers were interviewed. The results show that there is a process of co-creation of value thought and structured to promote the joint work of the different actors in order to produce results and good experiences in the service, with the occurrence of practices that involve the four dimensions of the DART model - Dialogue, Access, Risk-Benefit and Transparency -, although interactions can be expanded to consolidate practices and improve the process. The actors reveal that the set of efforts undertaken are rewarded by benefits that reach multiple spheres, involving society, science, the PPBio Network and the private sphere, through the value of use and esteem perceived by the subjects. Furthermore, this study proposed 11 guidelines, accompanied by 28 actions aiming to potentialize the dialogue, expand access, foment risk-benefit assessment and promote transparency, whose main lines potentially contribute to the consolidation and improvement of experiences in co-creation of value in the services of the PPBio Data Repository.